Analisis Niat dan Frekuensi Penggunaan Platform Social E-Commerce di Balikpapan Menggunakan Metode TAM - Rahmi, Muhammad Nur; Utamajaya, Joy Nashar (LPPM UNIKA Santo Thomas Medan, 2024)
This study analyzes the intention and frequency of using social e-commerce platforms in Balikpapan by employing the Technology Acceptance Model (TAM). The research focuses on understanding how perceived ease of use and perceived usefulness affect users' intentions to engage with these platforms and their actual usage frequency. Using a survey method, data were collected from 150 participants residing in Balikpapan. The results indicate that both perceived ease of use and perceived usefulness have a significant impact on users' intentions, which in turn influences their frequency of usage. These findings provide insights for platform developers and marketers aiming to enhance user engagement in emerging e-commerce markets.